Evidence for Higgs boson decay to a pair of muons - Sirunyan, A. M. (2021)
Evidence for Higgs boson decay to a pair of muons is presented. This result combines searches in four exclusive categories targeting the production of the Higgs boson via gluon fusion, via vector boson fusion, in association with a vector boson, and in association with a top quark-antiquark pair. The analysis is performed using proton-proton collision data at root s = 13 TeV, corresponding to an integrated luminosity of 137 fb(-1), recorded by the CMS experiment at the CERN LHC. An excess of events over the back- ground expectation is observed in data with a significance of 3.0 standard deviations, where the expectation for the standard model (SM) Higgs boson with mass of 125.38 GeV is 2.5. The combination of this result with that from data recorded at root s = 7 and 8 TeV, corresponding to integrated luminosities of 5.1 and 19.7 fb(-1), respectively, increases both the expected and observed significances by 1%. The measured signal strength, relative to the SM prediction, is 1.19(-0.39)(+0.40)(stat)(-0.14)(+0.15). This result constitutes the first evidence for the decay of the Higgs boson to second generation fermions and is the most precise measurement of the Higgs boson coupling to muons reported to date.